2019
DOI: 10.1186/s12913-019-4189-8
|View full text |Cite
|
Sign up to set email alerts
|

The German version of the high-performance work systems questionnaire (HPWS-G) in the context of patient safety: a validation study in a Swiss university hospital

Abstract: Background High performance work systems (HPWSs) are successful work systems in the context of safety climate and patient safety. The 10-item HPWS questionnaire is a validated instrument developed to assess existing HPWS structures in hospitals. The objectives of this cross-sectional study were to translate the English HPWS questionnaire into German (HPWS-G), to rate its content validity, and to examine its psychometric properties. Methods Content validity was examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
2
6
0
3
Order By: Relevance
“…They found that organizational cynicism mediates the relationship between high-performance work practices and intention to quit and that this indirect effect is dependent on the educational background of nurses which was a dimension of human resource management (Gkorezis, Georgiou, & Theodorou, 2018). Mielke et al, (2019) conducted a study with 281 healthcare professionals from a hospital in Switzerland. They used the 10-item HPWS scale, previously developed by Etchegaray and Thomas (2015) to ensure its cultural validity and reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that organizational cynicism mediates the relationship between high-performance work practices and intention to quit and that this indirect effect is dependent on the educational background of nurses which was a dimension of human resource management (Gkorezis, Georgiou, & Theodorou, 2018). Mielke et al, (2019) conducted a study with 281 healthcare professionals from a hospital in Switzerland. They used the 10-item HPWS scale, previously developed by Etchegaray and Thomas (2015) to ensure its cultural validity and reliability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In clinical practice, it was stated that the HPWS scale fits the model very well with its 9-item structure and can be used for in-hospital and inter-hospital comparison. However, the scale has only one dimension and requires some adaptation to express and re-evaluate psychometric properties in other clinical areas (Mielke et al, 2019). Wang, Xing, and Zhang (2019) investigated the dark side of HPWS in the health sector in a study conducted with 80 physicians, 125 nurses, and 18 other healthcare personnel from a hospital in China in 2019.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A six-dimension instrument that measures the physical environment: ambience (six items, Cronbach’s α 0.86), user-friendliness (six items, Cronbach’s α 0.76), layout (four items, Cronbach’s α 0.71), amenities (three items, Cronbach’s α 0.62), cleanliness (two items, Cronbach’s α 0.76), and adaptability (three items, Cronbach’s α 0.61), and presents values of internal consistency and dimensionality. The safety climate [ 30 , 31 , 32 , 33 , 34 , 35 ] and other safety-related concepts, such as patient safety culture [ 36 ] or safety attitudes [ 37 ], understood as all individual and group values that determine the commitment, style, and competence of an organization’s health and safety management. Worker relations [ 38 ] and its relationship to job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The safety climate [ 30 , 31 , 32 , 33 , 34 , 35 ] and other safety-related concepts, such as patient safety culture [ 36 ] or safety attitudes [ 37 ], understood as all individual and group values that determine the commitment, style, and competence of an organization’s health and safety management.…”
Section: Introductionmentioning
confidence: 99%